Bee-stings-inspired intelligently-sensitive electroactive microneedle with serrated structure for advanced electrical-stimulation-intervened chronic wound-management - Huie Jiang; Jiamin Zhang; Lijuan Chen; Qian Zhang; Fengqian Yang; Yifan Fei; Xing Chen; Xinhua Liu (International Journal of Extreme Manufacturing, 2025)
Rapidly-advancing microneedle-based bioelectronics integrated with electrical stimulation (ES) therapy exhibit significant potential for improving chronic wound management. Herein, bio-inspired by the serrated structure of bee-stingers, we developed a temperature-sensitive, two-stage microneedle-based electroactive platform (GP-PPy/PLA-MN) featuring rivet-like microstructures that integrates intelligent, precise drug-releasing, ES-transmission, and real-time wound-assessment monitoring for comprehensive chronic wound-management and diagnostic therapy. The bionic-design mechanically anchors the microneedle beneath the skin’s dermis, while GP-PPy/PLA-MN demonstrates versatile therapeutic characteristics, including outstanding biocompatibility, antimicrobial properties, and antimigratory origins. The GP-PPy/PLA-MN enables the sustained release of insulin at body temperature for up to 24 hours through the poly-N-isopropyl acrylamide grafted amidated-gelatin-based thermo-sensitive hydrogel at the needle-tip, thereby providing long-term stable blood glucose control. GP-PPy/PLA-MN indicates its potential as a novel bioelectronics-based patch to record the temperature and humidity during the wound-healing process, realizing significant wound diagnosis and real-time wound assessment, and fundamentally facilitating the therapeutic efficacy by supplying solid data to protect the clinical practice. Extensive in vitro and in vivo studies have demonstrated that GP-PPy/PLA-MN can provide effective ES and sustained drug release, thereby promoting chronic wound healing and increasing the wound healing rate by 20% compared to the control group after 14 days of treatment. This innovative approach combines bioelectronics with intelligent drug delivery and microneedling technology to effectively address the critical challenges of chronic wound management, offering promising prospects for precision diagnostics and therapeutic interventions.